Optical solitary waves and conservation laws to the (2+1)-dimensional hyperbolic nonlinear Schrodinger equation - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru (World Scientific Publ Co Pte Ltd, 2018)
This work studies the hyperbolic nonlinear Schrodinger equation (H-NLSE) in (2 + 1)-dimensions. The model describes the evolution of the elevation of water wave surface for slowly modulated wave trains in deep water in hydrodynamics, and also governs the propagation of electromagnetic fields in self-focusing and normally dispersive planar wave guides in optics. A class of gray and black optical solitary wave solutions of the H-NLSE are reported by adopting an appropriate solitary wave ansatz solution. Moreover, classification of conservation laws (Cls) to the H-NLSE is implemented using the multipliers approach. Some physical interpretations and analysis of the results obtained are also presented.
Keywords: Hyperbolic nonlinear Schrodinger equation; solitary wave ansatz solution; gray and black optical solitary wave solutions; conservation laws; multipliers approach